Retorika Guru Dalam Meningkatkan Kepercayaan Diri Siswa SMK Hutama Dengan Public Speaking - Eka Sapta Apriatna; Iin Soraya; Sari Ekowati Hadi (CV Edujavare Publishing, 2025)
This study analyzes the influence of teachers' rhetoric on students' self-confidence in public speaking at SMK Hutama. In the digital era 5.0, communication skills, especially public speaking, have become essential in education and social contexts. A qualitative descriptive method was used, with data collected from interviews, observations, and documentation of students and teachers. The results show that teachers' rhetoric significantly enhances students' self-confidence in public speaking. This research contributes to the development of communication science in education and is expected to serve as a reference for educators to improve their public speaking skills and students' self-confidence.